Adaptation of islamic religious education learning through digital technology for grade 12 students at smk muhamdiyah sintang - Nijo; Erwin; Muhammad Shalahuddin Al Awwaby; Rofi Wirawan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to analyze the adaptation of Islamic Religious Education (PAI) learning through digital technology for 12th grade students at SMK Muhammadiyah Sintang. In today's digital era, the use of technology in education is becoming an increasingly urgent need, especially to strengthen the effectiveness of the learning process. This research uses a descriptive qualitative method with a case study approach, and data analysis using data processing application Nvivo 12 Pro, focusing on the use of digital tools such as online learning platforms, educational software, and the role of social media in supporting Islamic Education learning. The results showed that the adaptation of digital technology has a significant impact on the learning process of Islamic Education at SMK Muhammadiyah Sintang. Covering the component of Islamic Education Learning Process with Digital Technology, although it looks smaller than the other two components, still has an important role in the analysis. This study recommends increasing digital literacy training for teachers, strengthening technological infrastructure in schools, and integrating interactive and collaborative learning methods using digital technology in PAI learning. Thus, it is expected that PAI learning can be more relevant and in accordance with the needs of the times.